Approximation technique for prosthetic design using numerical foot profiling - Bani Hashim, A.Y.; Abu Osman, Noor Azuan; Wan Abas, Wan Abu Bakar; Abdul Latif, L. (2011)
This work studies foot structure to develop a method that represents foot it in the form numerical profile. This profile is used to approximate the important parts for prosthetic foot design. This is done by a proper mapping of bones and joint which resulted in the creation of the kinematic structure. The structure simplifies the outlook of foot anatomy. The structure is then converted into graph that stores the information for vertex adjacency, edge incidence, and path. Further, this information is used to create the visual structures in the form of three distinct synthetic digital images. From these images the decision for important parts in the prosthetic foot design is made. Therefore, it is decided that the prosthetic foot should consist of foot-ankle mechnism and a flexible keel. Â© 2011 Springer-Verlag.